Interactive theorem proving : 6th International Conference, ITP 2015, Nanjing, China, August 24-27, 2015, Proceedings /: 6th International Conference, ITP 2015, Nanjing, China, August 24-27, 2015, Proceedings. (2015) - Unknown
No abstract available